Frecuencia de hematozoarios en bovinos de una región del caribe colombiano (2016)
The haematozoa have limited animal production in tropical regions, the climatic characteristics in tropical regions pro-vide ecological niches for the development of arthropods which are vectors of several species of the genres as Babe-sia, Anaplasma and Trypanosoma. The haematozoa pro-duce direct and indirect economic losses with implications on trade. The objective was to determine the frequency of haematozoa in cattle in the colombian Caribbean region. A descriptive cross-sectional study with a convenience sample, 12 farms were selected, where 310 blood samples from cattle of different ages, sex, racial group were taken, for the diagnosis of haematozoa by direct observation of extended blood and some hematology values. The highest frequency of haematozoa was for anaplasma sp. with 27.74%, followed by babesia sp. with 19.35% and trypanosoma sp. of 2.26%. It is indicating that this area is still endemic for haematozoa.